Perbandingan Metode Evaluasi Usability Antara Heuristic Evaluation dan Cognitive Walkthrough - Lit Malem Ginting; Grady Sianturi; Christina Vitaloka Panjaitan (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2021)
Usability evaluation is needed to identify and analyze usability problems in an application. This study will compare the results of usability evaluation with Heuristic Evaluation and Cognitive Walkthrough methods on the SIMRS Del Egov Center web from the aspects of usability problems found, the level of usability problems, and end user responses that will be evaluated using usability testing to find a more effective method of finding usability problems. Heuristic Evaluation will refer to the 10 heuristic principles proposed by Jacob Nielsen, while Cognitive Walkthrough, the expert will follow the task provided by the researcher. The results showed that the results of the evaluation conducted by Heuristic Evaluation found more usability problems in aspects: efficiency, memorability and satisfaction, while Cognitive Walktrough found more usability problems in aspects: learnability and error. In the severity rating aspect, Cognitive Walktrough is more effective in finding usability problems with a higher severity level, with an average of 3, while heuristic evaluation with an average of 2. In the aspect of end user responses to websites based on usability testing, Heuristic Evaluation has a SUS score which is higher at 57, while Cognitive Walktrough has an SUS score of 54.5. This shows that based on these three aspects, the Heuristic Evaluation method is better at finding usability problems in the SIMRS Del Egov Center application study object.